Analysis of the Elderly Class Program in Siumbut Baru Village, Kisaran Timur District - Sagala, Erlina Bernadet; Karnirius Harefa; Desideria Yosepha Ginting (JURNAL KESMAS DAN GIZI (JKG), 2025)
The Elderly Class Program is a form of non-formal education that aims to improve the quality of life of the elderly through health, social, and empowerment education. This study aims to analyze the implementation of the Elderly Class Program in Siumbut Baru Village, Kisaran Timur District, with a focus on implementation, assistance, obstacles, and its benefits for elderly participants. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation of the head of the health center, cadres, health workers, community leaders, and elderly participants. The results of the study indicate that the program has run according to its objectives, received support from various parties, and its benefits are felt by the elderly, especially in increasing understanding of healthy lifestyles, chronic disease management, and strengthening social functions. However, there are several obstacles such as the limited number of assistants and the inaccuracy of implementation time due to late participants. Routine evaluation and monitoring are carried out by officers and cadres to ensure that the quality of the program is maintained and obstacles can be overcome immediately. In conclusion, the Elderly Class Program in Siumbut Baru Village is an effective community education model, but requires strengthening in terms of human resources and cross-sector support to be more optimal